Oligo-Amenorrheic Polycystic Ovary Syndrome Patients Have Higher Risk For Cardiovascular Disease Compared to Hirsute Patients and Healthy Control - Özkaya, Enis; Çakır, Evrim; Küçüközkan, Tuncay (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: To evaluate the clinical, endocrine and cardiovascular disease risk profile differences in polycystic ovary syndrome (PCOS) patients who complain of hirsutism or oligo-amenorrhea. STUDY DESIGN: A total of 129 consecutive women underwent the screening investigation at Dr. Sami Ulus Women’s Health Teaching and Research Hospital between December 2009 and June 2010. There were 48 PCOS patients with hirsutism while 49 PCOS patients with oligo-amenorrhea and 32 healthy women included in the study. Body mass index (BMI), Waist/hip ratio (WHR) serum follicle stimulating hormone (FSH), luteinizing hormone (LH), progesterone, free testosterone, glucose, low density lipoprotein (LDL), total cholesterol, high density lipoprotein (HDL), triglceride (TG), high sensitive C reactive protein (hs-CRP), insulin, insulin sensitivity and carotid intima thickness (CIMT) were compared in PCOS patients who complain of hirsutism or oligo-amenorrhea and control group. RESULTS: Mean ages were similar among groups. There were significant differences among groups in terms of BMI, WHR, total cholesterol, LDL, TG, LH, fasting glucose, hsCRP, CIMT (p<0.05) (table 1). BMI, waist-hip ratio (WHR), total cholesterol, LDL, TG, LH, estrodiol, fasting glucose adjusted mean CIMT values were 0.40±0.01 mm, 0.49±0.012mm, 0.34±0.012mm (p<0.001) in hirsute, oligo-amenorrheic and control groups respectively. CONCLUSION: PCOS patients with oligo-amenorrhea without hirsutism have higher risk for cardiovascular disease (CVD) and abnormal lipid profile than patients with hirsutism without oligo-amenorrhea.